Galectins-1, -3 and -9 in leukemia: mechanistic insights and therapeutic translation - Wang, Tianning; Zhang, Yanxin; Guo, Yuchuan; Zhao, Mengmeng; Cai, Xiaojun; Feng, Shaojie (Frontiers in Immunology, 2025)
Galectins, β-galactoside-binding proteins, function as key regulators in pathological transitions, bridging tissue homeostasis to oncogenesis and inflammation through intracellular and extracellular mechanisms. Notably, they play a pivotal role in the pathogenesis of leukemia by interacting with glycoconjugates to promote tumor progression. Among them, Galectin-1 (Gal-1), Gal-3, and Gal-9 have been associated with multiple leukemia subtypes, such as acute myeloid leukemia (AML), acute promyelocytic leukemia (APL), B-cell precursor acute lymphoblastic leukemia (BCP-ALL), adult T-cell leukemia (ATL), and chronic lymphocytic leukemia (CLL). These galectins contribute to leukemic cell survival by modulating extracellular matrix (ECM) interactions, suppressing anti-tumor immune responses, and promoting immune escape. Their involvement in sustaining leukemic proliferation and immune evasion highlights their potential as therapeutic targets. Recent advancements in the development of galectin inhibitors provide promising avenues to disrupt these oncogenic pathways. However, distinct galectin isoform pathologies across diseases require highly selective therapeutics, and substantial carbohydrate recognition domain (CRD) structural homology combined with conserved β-D-galactopyranoside-binding mechanisms complicates specific inhibitor design. This review summarizes galectin-mediated mechanisms in leukemia biology, evaluates the potential of galectin-targeted therapies and offers insights for the development of specific inhibitors of Gal-1, -3, and -9 to promote clinical management and treatment efficacy.